2020
DOI: 10.2172/1756710
|View full text |Cite
|
Sign up to set email alerts
|

2019 Cost of Wind Energy Review

Abstract: 1 Project design life refers to the time in which the wind power plant is expected to operate (not referring to the turbine's design life for engineering or certification purposes).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 19 publications
2
92
0
Order By: Relevance
“…Figure 8 shows the average LCOE as a function of the flexibility range. The average LCOE values vary between 65 and 95 €/M W h, which is similar to the values described in the most recent technical reports [43,44]. It can be observed that the lowest LCOE is produced by the unchangeable system (case (iv)) followed by Strategy B and the baseline case.…”
Section: Size Of Flexibility Spacesupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 8 shows the average LCOE as a function of the flexibility range. The average LCOE values vary between 65 and 95 €/M W h, which is similar to the values described in the most recent technical reports [43,44]. It can be observed that the lowest LCOE is produced by the unchangeable system (case (iv)) followed by Strategy B and the baseline case.…”
Section: Size Of Flexibility Spacesupporting
confidence: 85%
“…Again, the parameters of the variables used in the example are summarized in Table 11. Function cf (t) represent a rapidly oscillating tendency between typical values reported in the literature [42,43,44]. The increment in the uncertainty over time is a modeling decision that attempts to capture the difficulty of predicting for such long time periods.…”
mentioning
confidence: 99%
“…The wind turbine is the most important part of a wind power plant and comprises nearly 20% of the overall LCOE of a floating offshore wind project (Stehly, Beiter, and Duffy 2020). Wind turbines are designed to efficiently convert the kinetic energy of the wind to aerodynamic energy (which turns the blades), mechanical energy (which turns the generator), and ultimately electrical energy (which is delivered to the grid).…”
Section: Wind Turbine Technology Trendsmentioning
confidence: 99%
“…The value proposition for deploying AWE systems offshore is primarily related to reduced foundation size, which makes up a significant portion of the CapEx of fixed-bottom and floating traditional wind turbines (Stehly, Beiter, and Duffy 2020). The low overturning moments of a tethered system directly connected to the foundation can drastically reduce the size, and therefore the cost, of the support structure (Kruijff and Ruiterkamp 2018).…”
Section: Viability For Offshore Windmentioning
confidence: 99%